2009
DOI: 10.1111/j.1523-5378.2009.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference of Circulating Ghrelin and Leptin Concentrations in Chronic Helicobacter pylori Infection

Abstract: There should be a gender difference to circulating total ghrelin levels, but not leptin levels, in response to H. pylori infection and its related chronic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
(63 reference statements)
1
31
1
2
Order By: Relevance
“…However, unlike our result, they found the fasting Ghrelin level to be negatively related to the BMI, to be similar in males and females and not change with the menopausal status (15 Among patients positive for HP, the plasma Ghrelin levels were found to be lower in males. In addition, a strong correlation was found between HP infection and acute and chronic inflammation scores associated with it and lower Ghrelin levels but only in males (17). Our chromogranin-A immunohistochemical analysis performed to evaluate the distribution of endocrine cells in LSG resection material revealed a mild increase in endocrine cells in 13 patients (39.4%), focal simple hyperplasia in 3 patients (9.1%), simple hyperplasia in 7 patients (21.2%) and micronodular hyperplasia in 3 patients (9.1%).…”
Section: Discussionmentioning
confidence: 89%
“…However, unlike our result, they found the fasting Ghrelin level to be negatively related to the BMI, to be similar in males and females and not change with the menopausal status (15 Among patients positive for HP, the plasma Ghrelin levels were found to be lower in males. In addition, a strong correlation was found between HP infection and acute and chronic inflammation scores associated with it and lower Ghrelin levels but only in males (17). Our chromogranin-A immunohistochemical analysis performed to evaluate the distribution of endocrine cells in LSG resection material revealed a mild increase in endocrine cells in 13 patients (39.4%), focal simple hyperplasia in 3 patients (9.1%), simple hyperplasia in 7 patients (21.2%) and micronodular hyperplasia in 3 patients (9.1%).…”
Section: Discussionmentioning
confidence: 89%
“…In general, although H. pylori infection down-regulated plasma and gastric ghrelin levels in subjects with normal renal function[28-30], these results also demonstrate the possibility that not only long-standing enhanced gastric mucosal inflammation induced by H. pylori infection but also gastric mucosal atrophy influenced plasma and gastric mucosal acyl- and desacyl-ghrelin levels[18]. In fact, in subjects with normal renal function, plasma ghrelin level was lower in H. pylori -positive patients with severe mucosal atrophy than in those without[18].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors claim that the level of circulating ghrelin is higher in women than in men [19] , but others maintain that it is similar in both sexes [20] and does not vary from childhood to adulthood [21] or undergo an age-related decrease [22] . In our studies we clearly demonstrated that in the case of gastric ghrelin, the hormone level was much higher in pre-menopausal women than in men (Figure 1).…”
Section: Discussionmentioning
confidence: 99%